Caution solidaire, une contrainte au developpement de la culture du cotonnier dans la region de Sikasso au Mali - AROUNA DEMBELE; JEROME ALOKO-N'GUESSAN (Cinq Continents, 2015)
Solidarity caution , a constraint for development of cotton cultivation in the region of Sikasso in Mali . Accompaniment finance institutions of cotton production have claimed cotton producers cooperatives societies (CPCS) to be the credit guarantee. From this collective guarantee, will appear the weaken operators in the (CPCS). So, the inability of these producers to reimburse their credit before the income distribution day push the (CPCS) to adopt a multitude distribution approa ches of cotton profit. The consequences of these approaches on the production are very patient now. The aim of this matter is to analyse distribution approaches of (CPCS) cotton profit by demonstrating their consequences on the cotton plant culture. Fo ur i nvestigations in the field have been undertaken. They have proved the cotton activity abandon by an important portion of producers (creditors and debtors). In one’s knows, the reduction of cotton culture surfaces is made by producers (creditors and debtors ) to simply maintain themselves in the cotton operators register. The revising of credit distribution instruction to producers has been planned as a solution for the cotton culture spinning.